Lymphovascular invasion is an independent prognostic factor for survival in pathologically proven N2 non-small cell lung cancer (Swiss Medical Weekly, 2021)
BACKGROUND We aimed to analyse the nodal spread of our non-small cell lung cancer pN2 cohort according to tumour location, the possible implications of an unusual spreading pattern, and other factors influencing postoperative survival after anatomical lung resection. METHODS In this retrospective observational study, clinical data was collected for 124 consecutive non-small cell lung cancer (NSCLC) patients with a pathological N2 (stage IIIA or B) undergoing anatomical lung resection at our institution between 2001 and 2010. Cox regression was used to analyse independent predictors of 5-year overall survival and recurrence-free survival. RESULTS A total of 105 patients were included in the final analysis. Tumour location in the right upper lobe and middle lobe was significantly more often associated with involvement of lymph node stations 2 and 4 than NSCLC in the right lower lobe (station 2: right upper vs right lower lobe, p = 0.001 and middle vs right lower lobe, p = 0.038; station 4: right upper vs right lower lobe, p